Arboreal Arthropods Species Diversity in Mangrove Forest Ciletuh, Sukabumi, West Java - Noor Farikhah Haneda; Cecep Kusmana; Bagas Kurnia Ramadhan (Jurnal Silvikultur Tropika, 2023)
This research was conducted in the mangrove areas Ciletuh, Sukabumi managed by Pokmasi Mandrajaya. Ciletuh mangrove area is occupied by mixed mangrove tree species. Mangrove is the habitat of a wide variety of arthropods and other canopy arthropods. Arthropods are one of the biotic components that play a role in multiple levels in an ecosystem. The existence of arthropods can be an indicator of the balance of the ecosystem. The purpose of this study was to estimate the abundance and diversity of arthropods in the canopy of Ciletuh mangrove areas. The study was conducted by analyzing vegetation, canopy arthropod catching by the beating-tray method, measurements of temperature and humidity. The results showed that canopy arthropods at 6 mangrove zoning in Ciletuh mangrove forest consisting of 21 families. Family that dominate in Ciletuh mangrove forest are family Formicidae in the class of Insecta and family Salticidae in the class of Arachnida. Keywords: arboreal arthropods, beating-tray, Ciletuh, mangrove